Database Education Enterprise - Ismail, Mohd Adlie Afiq; Jainal, Abdul Faris; Peter, Donna Bernadette; Milah, Stella; Madlan, Farah Adilah (2015)
Database Education Enterprise is located in shoplots. The exact adress is on the Jalan Sulaman, Kota Kinabalu, Sabah. We are expecting a good feedback of our business as it is new to enter the market There are no specific customers for our product, everybody can use our services without hesitation. The location that we actually choose is packed with students from various institutions and working people. Other than that, the walk ins customers must be attracted with the great service and hospitality. Although the service we provide is relatively new, we are really sure with the customer who use the service will be satisfied with the quality and outcome. Niche of the business will be the services we provide. Customers are eager to try new knowledge. We are using the finest material and sources for our lovely customers. Each staff of our business are qualified with accreditations and certifications. In terms of legal laws, we adhere the trading licensing from the state municipal.